The Gavino word association norms - Gavino, Jasmin A. (Philippine Journal of Psychology, 1971)
Norms for word associations to one hundred stimulus words from 1,000 University of the Philippines students are listed in this article. Essentially the Philippine norms were significantly different from the Russel and Jenkins and the Palermo and Jenkins list but was not significantly different from the Kent and Rosanoff list.